2011
DOI: 10.1111/j.1600-0560.2011.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous pigmented purpura: report of a case and review of the literature

Abstract: The pigmented purpuric dermatoses (PPD) are a group of diseases characterized by petechiae and bronze discoloration of the skin on the lower extremities. Histopathologically, extravasation of erythrocytes with hemosiderin deposition, a perivascular lymphocytic infiltrate centered on the superficial capillaries and endothelial cell swelling are seen. The granulomatous variant of PPD (GPPD) was described in 1996 and only 10 cases have been reported since in the literature, almost exclusively in patients of East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
1
29
0
3
Order By: Relevance
“…Since the first description of granulomatous variant of PPD in 1996 by Saito and Matsuoka in 1996, 12 additional cases have been published [1][2][3][4][5]. The majority of the patients, whose ages ranged from 22 to 71 years, were of East Asian descent.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of granulomatous variant of PPD in 1996 by Saito and Matsuoka in 1996, 12 additional cases have been published [1][2][3][4][5]. The majority of the patients, whose ages ranged from 22 to 71 years, were of East Asian descent.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it has been described in only 14 patients in the English literature (1)(2)(3). In addition, it was reported that approximately 29% of patients (4/14) showed serological evidence of autoimmune dysregulation, including positive ANA and rheumatoid factor tests (2, 3).…”
Section: Discussionmentioning
confidence: 95%
“…These reports suggested significant relationships between GPPD and autoimmune disorders (2^). In addition, Kaplan et al (2) recently reported the immunological profiles of GPPD and described the infiltration of significant numbers of CD4+ cells in granulomatous tissues, suggesting that, like sarcoidosis, immunological mechanisms might be associated with the formation of granuloma.…”
mentioning
confidence: 96%
“…Dependiendo de la extensión y de la morfología clínica, se reconocen distintas variantes 1,4,5,6 (Tabla 1).…”
Section: Discussionunclassified
“…Se debe hacer un análisis de la clínica, histología e inmunohistoquímica. 1 Hasta el momento no existe un tratamiento estándar. Si se identifica un agente etiológico, debe suspenderse y puede resolverse el cuadro.…”
Section: 8unclassified